Perancangan Dan Implementasi Half Bridge Dc – Dc Converter Dengan Kendali Arus Hysteresis - Masramdhani Saputra; Gian Fikih Yustiawan; Imron Ridzki; Sigit Setya Wiwaha; Binar Surya Gumilang (Elposys: Jurnal Sistem Kelistrikan, 2023)
DC-DC Converter is a direct voltage (DC) power supply device that is produced by converting DC input voltage into a lower or higher DC output voltage. In its development, the application of DC-DC Converter allows an electronic device to function with a small energy source, where the output voltage can be varied as needed. DC-DC Converters have been widely developed because they have various advantages, including: simpler form and has high efficiency. In this thesis, an Arduino Mega 2560-based current controller will be implemented. The type of current controller implemented is hysteresis current control with the well-known, tested and proven considerations. Current control works if the inductor current rises from the lower limit of the hysteresis band to the upper limit then the switch will be turned off (inductor current above the upper reference Ip.Ref) and if this current drops from the upper limit to the lower limit the switch will be turned on (current inductor under low frequency Iv.Ref). This current control also has advantages in overcurrent protection such as when there is a short circuit in the load.